Clinico-therapeutic studies on downer cows - Prasanna K (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2005)
he study entitled “Clinico-therapeutic studies on downer cows” was carried out in twelve cows, which did not respond to the treatment by local Veterinarians. Two of the cows presented at Veterinary Hospital, Mannuthy and other ten field cases from Trissur district formed the subjects for this study. All the animals were subjected to detailed clinical examination and all parameters under study viz., signalment, history, physical examination haematology, serum biochemistry and treatment response were carried out. The data obtained were analysed statistically. Highest percentage of occurrence was seen in cross bred Jersey cows and in old age group. Seventy five percentage of cows were with in first week of lactation, eight percentage at eighth month of gestation and sixteen percentage in mid lactation. Occurrence was recorded during the period from May 2004 to May 2005. All the cows were fed on a compounded concentrate ration and quantum of feed were not proportional to the milk production. They were maintained on concrete floors and had no history of a fall or exposure to adverse climatic condition. All the cows were in sternal recumbency at the time of presentation and were alert without other clinical signs. Frequent attempts to rise and changing the sides by their own was common in most cows. All the physiological parameters were with in the normal range. Feed in take, urination, defecation and rumination were normal. Bruises over hock, elbow and tuber coxae were seen as common complications. One cow that developed mastitis and cows with Amphistome infestation were concurrently treated. Statistically significant (P<0.05) increase in total leukocyte count and neutrophilia were recorded in cases with traumatic injuries and subsequent inflammation over elbow joint, hock, tuber coxae and stifle. Mild lymphopenia was also seen. Biochemical alterations included hypocalcaemia and hypophosphatemia and the calcium phosphorus ratio was found to be reduced to 1.69 before the treatment. The general line of treatment adopted for downer cows in the present study were administration of calcium magnesium borogluconate 450-900ml intravenously, inorganic phosphorus-40% (10 –20 ml) either intravenously or intramuscularly, vitamin AD3E combination having Vitamin D3 @ 2.5 lakh IU intramuscularly, and multivitamin preparation 10 ml intramuscularly to all animals. In addition supportive treatment with non steroidal anti inflammatory analgesic drugs of meloxicam group (@ 0.5 mg/kg BW) 30ml intravenously or salicylate phenylbutazone combination (@ 4 mg /kg BW) 15ml intravenously or intramuscularly (six cases each) were administered. Dextrose 25% was also administered intravenously for clinically weak animals. Dosage and frequency varied according to biochemical profile, clinical picture and response to therapy. Out of twelve cows, seven cows recovered from downer state. Three cows were under treatment for 4 to 5 days, two cows for 3 days and seven cows for two days. Serum calcium, phosphorus ratio in the recovered animals returned to normal of 2.1: 1. After treatment five cases were either slaughtered due to severe traumatic injury or owners were unwilling to treat the animal.